Design Of A Web-Based Medicine Sales Information System At The Dety Pharmacy - Heni Wulandari; Winda Erika (Jurnal Scientia, 2024)
The development of online stores or e-commerce plays a very important role for entrepreneurs who want to market their products easily and get more profits. Dety Pharmacy is a form of business operating in the pharmaceutical sector, precisely located in Medan City. In marketing its products, Dety Pharmacy is still very far from using information technology, so the development of its business tends to be slow. The Web-Based Medicine Sales Information System is very effective in enabling online sales. Design of a Web-Based Drug Sales Information System at Dety Pharmacy using Dreamweaver software, PHP and MySQL programming languages. In designing the information system, several views are displayed which include the administrator page display, pharmaceutical product data, drug brand data, drug category data, print order details, and the shopping cart page. Based on the results of system testing, it can be concluded that designing a web-based drug sales information system at the Dety Pharmacy can speed up the drug ordering process and make it easier for admins to search for data and process data. Apart from that, designing a web-based drug sales information system at the Dety Pharmacy can increase sales turnover and advance the business.